survey the Sexual Behavior of Intellectual Disability adolescents during Sexual Puberty from the point of view of Parents and Teachers - Seyed Mohammad Ali Miri; Gholam Ali Afroz; Bagher Ghobari Bonab; Majid Ghadami (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2019)
Aim and Background: The occurrence of sexual behavior by young people with intellectual disability can create many problems for families and teachers. Therefore, the purpose of this study was to identify the sexual behaviors of adolescents with intellectual disability from the viewpoint of parents and teachers.